New Records of Lake Baikal Leech Fauna: Species Diversity and Spatial Distribution in Chivyrkuy Gulf - Irina A. Kaygorodova; Nikolay M. Pronin (The Scientific World Journal)
The study of several Lake Baikal leech collections offered us the possibility to determine species diversity in the Chivyrkuy Gulf, the biggest one in the lake. As a result, the first information on the Chivyrkuy Hirudinea fauna (Annelida, Clitellata) has been revealed. There are two orders and four families of leeches in the Chivyrkuy Gulf: order Rhynchobdellida (families Glossiphoniidae and Piscicolidae) and order Arhynchobdellida (families Erpobdellidae and Haemopidae). In total, 22 leech species and 2 subspecies belonging to 11 genera were identified. Of these, 4 taxa belong to the family Glossiphoniidae (G. concolor, A. hyalina, A. heteroclita f. papillosa, and A. heteroclita f. striata) recorded in Baikal for the first time. Representatives of 8 unidentified species (Glossophinia sp., Baicaloclepsis sp., Baicalobdella sp., Piscicola sp. 1, Piscicola sp. 2, Erpobdella sp. 1, Erpobdella sp. 2, and Erpobdella sp. 3) have been also recorded. The checklist gives a contemporary overview of the species composition of leech parasites, their hosts, and distribution within the Chivyrkuy Gulf. The analysis of spatial distribution has shown that the leech species diversity is correlated with the biological productivity of the bay. The most diverse community of leech species is detected in the eutrophic zone of the lake.